History of extracardiac/cardiac events in cardiac amyloidosis: prevalence and time from initial onset to diagnosis. (29th October 2021) - Kharoubi, Mounira; Bézard, Mélanie; Galat, Arnault; Le Bras, Fabien; Poullot, Elsa; Molinier‐Frenkel, Valérie; Fanen, Pascale; Funalot, Benoit; Moktefi, Anissa; Lefaucheur, Jean‐Pascal; Abulizi, Mukedaisi; Deux, Jean‐François; et al.
Abstract: Aims: Cardiac amyloidosis (CA) has a poor prognosis which is aggravated by diagnostic delay. Amyloidosis extracardiac and cardiac events (AECE and ACE) may help improve CA diagnosis and typing. The aim of this study was to compare AECE and ACE between different CA types and assess their relationship with survival. Methods and results: This retrospective cohort study conducted in France from June 2008 to May 2019, at the Henry Mondor Hospital. This cohort included 983 patients with CA. Mean age at inclusion was 73.1 ± 11.4 years, 726 (75.1%) were male and the mean body mass index was 24.5 ± 4.1 kg/m 2 . Among them, 321 had immunoglobulin light chain (AL) amyloidosis, 434 had wild‐type transthyretin (ATTRwt), and 212 had hereditary transthyretin (ATTRv). The first AECE and/or ACE occurred at a mean age of 63 ± 11 years for AL and ATTRv, and 70 ± 12 years for ATTRwt ( P < 0.01). The median (Q1–Q3) delay between declaration of the first events and diagnosis varied from 11.1 (5.9; 34.8) months for AL to 92.2 (39.0; 174.7) months for ATTRwt ( P < 0.01). The nature of the onset of AECE or ACE varied based on amyloidosis type, heart failure symptoms for AL (26%) and integumentary symptoms for ATTRv with cardiologic or mixed phenotype (39%) and ATTRwt (42%). In AL and ATTRwt, a short delay between the onset of the first AECE or ACE and diagnosis was associated with reduced survival rate (log‐rank test P ‐value <0.01). Conclusions: This study highlights the impact of amyloidosis type and evolution on diagnostic delay and on prognosis. Physicians must be aware and vigilant in front of extracardiac and cardiac events to considerably improve early diagnosis of amyloidosis.